The use of perforator flaps for the reconstruction of sacral defects: Ten-year experience - Hao-Yu Chiao; Shun-Cheng Chang; Chang-Yi Chou; Yuan-Sheng Tzeng; Shyi-Gen Chen; Chin-Ta Lin (Formosan Journal of Surgery, 2018)
Background: Despite advances in reconstruction techniques, sacral defects continue to challenge surgeons. The perforator flap preserves the entire contralateral side as a future flap donor site and the gluteal muscle itself on the ipsilateral side to minimize donor-site morbidity. Materials and Methods: Between April 2003 and March 2013, data obtained from 60 patients with sacral defects reconstructed with perforator flaps were retrospectively analyzed. Results: We analyzed the sacral defects reconstructed with three different perforator flaps into the following groups: group 1, 30 patients with superior gluteal artery perforator flaps, (average flap size was 83.8 cm2); Group 2, 19 patients with parasacral perforator flaps (average flap size was 94.2 cm2); and Group 3, 11 patients with inferior gluteal artery perforator flaps (average flap size was 85.8 cm2). The overall flap survival rate was 93.3% (56/60). Conclusion: Perforator flaps are a reliable option for soft-tissue defect reconstruction as they provide a sufficient amount of tissue to cover large sacral defects. We recommend perforator flaps as a viable alternative in the management of sacral defects that cannot be reconstructed with primary closure or local fasciocutaneous flaps.